Analysis of Implementation the Project of Pancasila Student Profiles Reinforcement at Local Wisdom Theme Phase B SD Advent Merauke - Dewi Puji Rahayu; Karlina Wong Lieung (Technium Social Sciences Journal, 2023)
This study intends to show how a project to enhance Pancasila students’ profile on the local wisdom theme Phase B of Merauke Adventist Elementary School was implemented. This study is qualitative in nature. The principals of the schools and the instructors of the fourth grade at Merauke Adventist Elementary School served as the study’s subjects. Purposive sampling was employed to choose the study’s participants. using interviews, observation, and documentation to gather data. Techniques for data analysis involve gathering data, reducing it, presenting it, and drawing conclusions. The project’s execution at Merauke Adventist Elementary School to strengthen the Pancasila project with the topic of local knowledge was carried out in two stages, namely the stages of developing the P5 project and managing the P5.